Functionally Diverse Inflammatory Responses in Peripheral and Liver Monocytes in Alcohol‐Associated Hepatitis. Issue 10 (4th August 2020) - Kim, Adam; Bellar, Annette; McMullen, Megan R.; Li, Xiaoxia; Nagy, Laura E.
Abstract : Alcohol‐associated hepatitis (AH) is an acute inflammatory disease in which gut‐microbial byproducts enter circulation and peripheral immune cells infiltrate the liver, leading to nonresolving inflammation and injury. Single‐cell RNA sequencing of peripheral blood mononuclear cells isolated from patients with AH and healthy controls paired with lipopolysaccharide (LPS) challenge revealed how diverse monocyte responses are divided among individual cells and change in disease. After LPS challenge, one monocyte subtype expressed pro‐inflammatory genes in both disease and healthy controls, while another monocyte subtype was anti‐inflammatory in healthy controls but switched to pro‐inflammatory in AH. Numerous immune genes are clustered within genomic cassettes, including chemokines and C‐type lectin receptors (CTRs). CTRs sense byproducts of diverse microbial and host origin. Single‐cell data revealed correlated expression of genes within cassettes, thus further diversifying different monocyte responses to individual cells. Monocyte up‐regulation of CTRs in response to LPS caused hypersensitivity to diverse microbial and host‐derived byproducts, indicating a secondary immune surveillance pathway up‐regulated in a subset of cells by a closely associated genomic cassette. Finally, expression of CTR genes was higher in livers of patients with severe AH, but not other chronic liver diseases, implicating secondary immune surveillance in nonresolving inflammation in severe AH. Abstract :